The effect of discovery learning model assisted by flipbook media on student learning outcomes on plantae material class X senior high school - Fitriyana; Kurnia Ningsih; Laili Fitri Yeni (Assimilation)
This study aims to measure the effectiveness of the Discovery Learning model using Flipbook media in enhancing the understanding of Plantae material. This research adopted a quasi-experimental design with a non-equivalent control group. Two entire classes were selected as samples: class X MIA 2 as the experimental group and class X MIA 4 as the control group. The research instrument was a 20-item multiple-choice test, administered as a pre-test and post-test. The comparison of average scores between the experimental group (15.89) and the control group (15.17) showed an improvement in the experimental group. Statistical analysis using the Mann Whitney U test indicated no statistically significant difference between the two learning groups. The 13.68% improvement in students' learning outcomes in the Plantae material may be attributed to the application of the learning model used in this study.